2010
DOI: 10.1128/jvi.00633-10
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Quantification of Chronic Wasting Disease Prions

Abstract: Cell-based measurement of prion infectivity is currently restricted to experimental strains of mouse-adapted scrapie. Having isolated cell cultures with susceptibility to prions from diseased elk, we describe a modification of the scrapie cell assay allowing evaluation of prions causing chronic wasting disease, a naturally occurring transmissible spongiform encephalopathy. We compare this cervid prion cell assay to bioassays in transgenic mice, the only other existing method for quantification, and show this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 23 publications
1
108
0
Order By: Relevance
“…We previously developed a cell-based assay for quantifying CWD prions with sensitivity comparable with the CWD bioassay in susceptible Tg mice (16). We used this cervid prioncell assay (CPCA) to compare levels of CWD prions in Elk21 + with quinacrine-treated cells.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed a cell-based assay for quantifying CWD prions with sensitivity comparable with the CWD bioassay in susceptible Tg mice (16). We used this cervid prioncell assay (CPCA) to compare levels of CWD prions in Elk21 + with quinacrine-treated cells.…”
Section: Significancementioning
confidence: 99%
“…Our first approach was to assess the efficacy of compounds with known effects on rodent prions. Consistent with its effect on mouse prion infectivity, sustained treatment of Elk21 + cells with dextran sulfate 500 (DS-500) resulted in PrP Sc clearance, which did not reemerge in the resulting Elk21 − cells after more than 40 passages, and inoculation of susceptible transgenic (Tg) mice showed that Elk21 − cells were cured of CWD prion infection (16). The present study was initially designed to assess the effects of quinacrine on CWD.…”
mentioning
confidence: 99%
“…12 Several other groups also reported the permissiveness of RK13-cells expressing mouse, bank vole, deer and elk PrP C to propagate prions from the corresponding species. [13][14][15] Scrapie prion propagation was not observed in various established cell lines (non-transfectants) that naturally express endogenous PrP C , including the 2 cell lines derived from fetal tissues of goats. 20 Therefore, we decided to use the RK13 cell line to express caprine PrP C and then assess its ability to propagate brain-derived classical caprine scrapie prion isolates.…”
Section: Cprk13 Cells Support Propagation Of Classical Caprine Scrapimentioning
confidence: 99%
“…The susceptibility of RK13-based transfectants to corresponding rodent-and cervid-derived prion propagation has been reported. [13][14][15] In this study, we demonstrate for the first time that RK13 cells stably expressing caprine PrP C (cpRK13) was permissive to certain classical caprine scrapie prion isolates prepared from the brain tissues of scrapie-infected goats and ovinized transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…13 -15 Cell-based assays for the titration of prion infectivity Due to substantial methodological advancements it has become possible to titrate the infectivity of certain murine scrapie prions (22L, RML) in quantitative cell-based assays using subcloned neuroblastoma (N2a) cells. 10 -12 Furthermore, RK13 cells transgenically expressing PrP from mouse, sheep or cervids were shown to allow the titration of RML prions, 16 a natural sheep scrapie isolate (PG127), 16 and chronic wasting disease agent, 17 respectively.…”
mentioning
confidence: 99%